9 - Participatory Development and Non-Governmental Organisations in Sudan: Expectations and Realities - El-Gack, Nawal (Africa Development, 2021)
This article describes and analyses the roles and contributions of non- governmental organisations in Sudan. There is a strong belief that involving local people in development activities would be achieved through community organisations. As a result, when implementing participatory development interventions, there is a tendency to rely on non-governmental organisations (NGOs) at national and regional levels, and support the formation of community organisations at grassroots level. To understand the concepts of these practices, this article will provide a brief review of NGOs’ theories and in-depth analysis of Sudanese NGOs’ performance and contributions. It suggests that there is a need to encourage and support the establishment of effective networks and links between government institutions local community organisations, private sectors and international organisations. Moreover, the article argues that international organisations with genuine intentions to reach the impoverished communities should be aware of their local partners’ vision and investigate how genuine democratic and accountable non-governmental organisations are promoting participatory development approaches. Information about NGOs is based on a field research conducted 2007. I used focus group discussion and semi-structured interviews to explore the participants’ perceptions and experiences.